Book review: Chris Coulter. Bush Wives and Girl Soldiers: Womens Lives through War and Peace in Sierra Leone . - Toomas Gross (Suomen Antropologi)
COULTER, CHRIS. Bush Wives and Girl Soldiers: Womens Lives through War and Peace in Sierra Leone. Ithaca: Cornell University Press, 2009. Pp. 290. ISBN: 978-0-8014-7512-2.